Експресія творів сучасного мистецтва. Живопис - Прокопович, Тетяна Анатоліївна; Prokopovych, Tetiana A. (Харківська державна академія дизайну і мистецтв, 2016)
У статті проаналізовано експресію творів сучасного мистецтва на основі картин найдорожчих сучасних українських художників. Викладено різновекторність наукових підходів до вивчення феномену художника. Висвітлено аспекти психологічного дослідження емоційності художників і її проекцію на мистецьку діяльність. На основі теоретичного і емпіричного дослідження виявлено проблеми взаємодії емоцій і творчої діяльності художників. Розглянуто прояви експресії у творах сучасних художників В. Цаголова. О. Ройтбурда, А. Криволапа, М. Вайсберга. Зауважено, що експресія є одним з складових успіху у сучасному мистецтві, так як, передана на полотно сила прояву почуттів та переживань, підсилює несвідомий вплив мистецтва на глядача.

The article analyzes the expression of contemporary art paintings on the basis of the most expensive paintings of contemporary Ukrainian artists. Different scientific approaches to studying the phenomenon of the artists are revealed in this article. This article describes the aspects of psychological research of artists’ emotionality and its projection on artistic activity. Based on theoretical and empirical research, the problems of interaction between emotions and creative activity of artists are found. Manifestations of expression in the works of V. Tsaholov, A. Roytburd, A. Kryvolap, M. Weisberg are revealed. The context of individual preferences of an artist makes an impact on all the aspects of life of the creative personality, expressiveness and imagery of his works determines their cognoscibility and actuality on the art-market. This symbiosis implies the presence of the factors of expression in the paintings of artists. Expression, in its turn, has an impact on the format of artistic activity which involves research of the problem on the border of two sciences - art and psychology. Modern context of the scientific research declares qualitatively new projection of its analysis, aimed at the comprehension of the complexity and mysteriousity of the structure of the creative personality and actuality of its works of art on the modern art-market. Artistic activity is the only non-verbal tool that reveals the intense feelings and emotions, that is why with the help of images an artist can better reveal his emotional distress. Passing the images of visual perception through his nervous system, he creates his own notional objects which are selected from reality. Through images, colour palette and plot, artists express their emotions, get rid of heavy thoughts, dislodge taboo topics from their minds. Bright emotional states that are peculiar to artists are manifested through the expression of contemporary art paintings. Modern artists engage and actively respond to the state of society and emotional moods in it. In their works they use reflections of the mind and visual responses, artists express the maximum emotional conglomerate of their internal state, its emotional borders and social imprint in the mind. Internal feelings and emotional processes, occurring inside the artist, affect the transfer of expression in his works. Expressiveness and emotional colouring of the painting is realized through the use of imagery and subjectivity and is directly linked to the cultural and social life. Expressive factor in art is one of the most important factors of direct influence of works of art to the viewer. In the works of the most expensive Ukrainian contemporary artists expression can also be found. For example in the paintings of V. Tsagolov expression is manifested through a combination of brutality and sensuality, mythology and popular culture. Through the overblown imagery of fairy-tale characters, aliens, criminal boys and office relationship the artist shows the topics that embarrass the public - the dehumanization of society and the collapse of spirituality. A. Roytburd in his works combines incongruous, he comprehensively expresses his vision of degradation of society, using images he tries to change the background and the focus of vision and perception, the context of the viewer’s thought. The artist shifts the emphasis to rethink and create a new viewpoint at the classical and timeless stories where abstraction and biblical characters are intertwined. Combining bright palette of colours on a dark background, the artist does not only consciously influence by the plot of the work, but also makes a subconscious effect on the viewer using the colour. A. Kryvolap creates mystical monochromatic, harmoniously combined or in contrasting open colours paintings. The main expressive technique of his paintings, which provokes the rise of emotions and the viewer’s creative vision, is the depiction of space, which is formed by pure colours in the monochromatic palette or in the palette of harmonious combination of contrasting colours, which due to its secondary properties influences the mind, delights the audience, causing the expression. M. Weisberg, in his works, reveals expressivity quite colourfully, developing the ideas of humanism confrontation and recalcitrance. The artist connects his creativeness with the reality, develops topics which embarrass the public, showing sharp social and political relations in the country. In the paintings of the artist, expression is revealed through a combination of means and styles, profound lyricism, understanding of time as a catastrophic space of human existence. It is sometimes complicated by formlessness, diversity, plot and symbolism, revealed through the strengthening of silhouettes, colours and shapes on a dark background. It is revealed that the expression of contemporary art paintings is a kind of emotional sublimation of artists, their visual senses and perception of the world. It is mentioned that the expression is one of the components of success in contemporary art, since transferred to canvas, the strength of manifestation of feelings and experiences in various forms, enhances the impressive effect on the viewer.
Expression of contemporary art paintings. Painting
Keywords: експресія; мистецтво; емоції; живопис; сучасне мистецтво; expression; emotions; art; painting; contemporary art; artists